2019
DOI: 10.1111/cdev.13247
|View full text |Cite
|
Sign up to set email alerts
|

The Production Effect Improves Memory in 7‐ to 10‐Year‐Old Children

Abstract: The production effect-whereby reading words aloud improves memory for those words relative to reading them silently-was investigated in two experiments with 7-to 10-year-old children residing in Brisbane, Australia. Experiment 1 (n = 41) involved familiar printed words, with words read aloud or silently appearing either in mixed-or blocked-list formats in a within-subject design. Recognition for words read aloud was better than for those read silently, an effect consistent across both list formats. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
(104 reference statements)
2
15
0
Order By: Relevance
“…Children were trained on images of objects depicting familiar words in different conditions: LOOK (children see the image in silence), LISTEN (children see the image and hear the corresponding word), and SAY (children see the image and produce the corresponding word). In line with theories and models that predict an interaction between task demands and performance on tasks, such as PRIMIR (Werker & Curtin, 2005), and consistent with prior work by Icht and Mama (2015) and Pritchard, Heron-Delaney, Malone, and MacLeod (2019), we predicted that older children would recall more words from the SAY than from the LOOK or LISTEN training conditions. However, we also expected the effect of production could vary as a function of age, for example, younger children might either show an attenuation or a reversal of the production effect, since young children's less mature system may have more difficulty processing words that were produced aloud (Zamuner, Strahm, Morin-Lessard, & Page, 2018).…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Children were trained on images of objects depicting familiar words in different conditions: LOOK (children see the image in silence), LISTEN (children see the image and hear the corresponding word), and SAY (children see the image and produce the corresponding word). In line with theories and models that predict an interaction between task demands and performance on tasks, such as PRIMIR (Werker & Curtin, 2005), and consistent with prior work by Icht and Mama (2015) and Pritchard, Heron-Delaney, Malone, and MacLeod (2019), we predicted that older children would recall more words from the SAY than from the LOOK or LISTEN training conditions. However, we also expected the effect of production could vary as a function of age, for example, younger children might either show an attenuation or a reversal of the production effect, since young children's less mature system may have more difficulty processing words that were produced aloud (Zamuner, Strahm, Morin-Lessard, & Page, 2018).…”
supporting
confidence: 87%
“…Children then saw words printed in black (40 trained, 20 untrained) and were asked to verbally indicate whether they remembered the words from training. Across two experiments with real words and novel words, Pritchard et al (2019) found a recognition advantage for items that were read aloud over those that were read silently. This is consistent with the adult literature using reading paradigms and extends the previous findings from children using images and auditory stimuli (Icht & Mama, 2015) but diverges from , who found a reverse production effect.…”
mentioning
confidence: 95%
See 3 more Smart Citations